(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research aimed to reveal the reality of electronic infidelity and the reality of family stability among a group of Jordanian spouses representing the study sample. It also aimed to detect the existence of a statistically significant positive correlation relationship at (0.05) level of significance between electronic infidelity and family stability among a group of Jordanian spouses representing the study sample. The study sample consisted of (94) husbands and wives. The researcher adopted the Electronic Infidelity Scale and the Family Stability Scale as the study instruments. The researcher also adopted the analytical descriptive approach as the study approach. The researcher reached several results, including the following: The reality of electronic infidelity among a group of Jordanian spouses representing the study sample scored (very weak), The reality of family stability among a group of Jordanian spouses representing the study sample scored (very high), There is a negative correlation relationship between electronic infidelity and family stability, There are no statistically significant differences on the Electronic Infidelity Scale and the Family Stability Scale in the light of the following variables (gender - number of children - number of years of marriage), The researcher offered a number of recommendations, the most important of which are the following: the necessity of increasing the understanding between husbands and wives in the Jordanian society and working on closing the gap between thoughts and orientations to increase the levels of family stability and reduce marital infidelity.